The Effectiveness of Audio-Based Talking Stick Method in Civics Education to Improve Students' Communication Skills in Grade V Elementary School - Achdan Defa Al Malik; Murfiah Dewi Wulandari (Eduvest - Journal of Universal Studies, 2024)
The purpose of this study was to determine the effectiveness of the Audio Media-Based Talking Stick Method in Civics Learning to Improve the Communication Skills of Grade V Elementary School Students. This research uses a quantitative approach method. To improve the communication of grade V (Five) elementary school students, researchers used the audio media-based talking stick learning method. This research was conducted at SD 02 Bakalrejo with a sample size of 20 students. Researchers get results where there is an increase in the ability to communicate class V (Five) students with the Audio Media-Based Talking Stick learning method can be seen from the results of a significance value that is smaller than the probability value of the Independent Sample T Test test (0.000 <0.05), meaning that there is an average difference in the results of students' communication skills between the Audio Media-based Talking Stick learning method and conventional / ordinary methods. The difference can also be seen from the average value of the control class results of 45.80 and there is an increase seen from the Experiment class of 63.50. So the resulting effectiveness of the Audio Media-Based Talking Stick method in Civics learning provides an increase in communication of grade V (Five) students by 17.7%. It is hoped that the results of this study can be used to help teachers and other researchers in presenting more inclusive and interactive learning.